Dietary mannan oligosaccharide enhances growth and survival of juvenile tiger shrimp Penaeus monodon against experimental challenge with Vibrio harveyi and white spot syndrome virus - Felix, N.; Arasi, P. Kalaimani; Manikandan, K. (Indian Journal of Fisheries, 2020)
A 45-days feeding trial was conducted on juvenile tiger shrimps Penaeus monodon of size 0.997Â±0.098 g with diets containing Mannan oligosaccharides (Mos) at three graded levels (0.1, 0.2 and 0.3%). Maximum weight gain (1.353 g) was achieved in shrimps fed with 0.3% Mos concentration, followed by 0.2% Mos (1.224 g). Best feed conversion ratio (FCR) of 2.406 was registered in 0.3% Mos groups. Results indicate that there was a significant difference (p<0.01) in weight gain and FCR among the treatments. However, no statistical differences were observed on the specific growth rate (SGR), mean feed intake and survival rate. Feeding trial was followed by a 10 days challenge study with Vibrio harveyi by intramuscular injection and white spot syndrome virus (WSSV) by feeding WSSV infected tissues. Significantly higher survival rate was observed in the shrimp groups fed with 0.3% Mos (66.67%) than the other treatments when challenged with V. harveyi. Tiger shrimps fed with 0.3% Mos challenged with WSSV showed a significantly higher survival rate (66.67%), followed by 0.2% Mos (50%), 0.1% Mos (25%) and control (25%) on day 5 post-challenge. However On day 10 post-challenge with WSSV, except in the groups fed with 0.3% Mos (16.67% survival), 100% mortality was noticed in all other diet groups. Therefore, it is concluded that dietary administration of Mos at 0.3% would enhance the growth and survival of tiger shrimp against V. harveyi. With respect to WSSV challenge, it appears that, though Mos at 0.3% had a positive effect on the shrimp, higher survival was not observed. Whether additional increment in Mos supplementation in the diet would positively affect the survival of tiger shrimps post-WSSV challenge, needs to be investigated further. Keywords: Mannan oligosaccharides, Penaeus monodon, Survival, Vibrio harveyi, White spot syndrome virus, WSSV